The Developing of English-Speaking Skill of the Students at Islamic Junior High School by Using Picture - Suparlan Suparlan; Ahmad Zuhri Rosyidi (Institut Agama Islam Negeri Palopo, 2022)
The purpose of this study was to develop the English communication skill of the second class of the students of MTs Darul Aminin NW Aikmual Lombok Tengah NTB by using picture to determine the use ofpicture to develop the speaking skill and determine the students' speaking skill after using picture. The study is conducted at the second class of the students of MTs Darul Aminin NW Aikmual Lombok Tengah NTB. There were 40 Students consisting of 26 boys and 16 girls as the subject of the study.This study uses classroom action research (CAR). The results of this study are as follows. First, by applying the picture, it can develop the students' speaking skill. Students able to communicate communicatively, sequentially, well, and correctly, this can be seen after classroom action research has been carried out. Second, by applying the picture to the students in the teaching and the learning process in order to developthe students' English speaking skill, it can be seen through the increasing the results of the scores of English speaking skill.Therefore, it was suggested to the teachers especially the English teachers to used the picture as the teaching material to solve the students' problems not only in the picture but in other English skills too.